2015
DOI: 10.1080/00224545.2015.1047439
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Envy

Abstract: The aim of this study was to examine the relationship between individual attributes and envy, and to determine how envy may impact personal response variables in the workplace. To address these issues we apply Vecchio's theory on antecedents and consequences of envy (1995) as a theoretical framework. The present study relied on a cross-sectional measurement design. A total of 135 leaders and 772 followers employed in business organizations participated. SEM analysis shows that span of supervision serves as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 35 publications
3
71
0
Order By: Relevance
“…As a result, when followers feel envious toward others who have higherquality LMX relationships, they are more likely to adopt destructive interpersonal behaviors to undermine the target. Research has shown that envy has been deemed to have the power to profoundly affect interpersonal relationships, creating conflict that can manifest as violence and aggression (Vecchio, 2000;Thompson et al, 2016). Previous research has supported the notion that an envious person may harm the envied person, which negatively alters the envied person's better outcomes (Kim & Glomb, 2014).…”
Section: The Mediating Role Of Being Enviedmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, when followers feel envious toward others who have higherquality LMX relationships, they are more likely to adopt destructive interpersonal behaviors to undermine the target. Research has shown that envy has been deemed to have the power to profoundly affect interpersonal relationships, creating conflict that can manifest as violence and aggression (Vecchio, 2000;Thompson et al, 2016). Previous research has supported the notion that an envious person may harm the envied person, which negatively alters the envied person's better outcomes (Kim & Glomb, 2014).…”
Section: The Mediating Role Of Being Enviedmentioning
confidence: 97%
“…Third, our study shows that interpersonal comparison within a team could arouse emotional responses among team members. Given that extant research has identified many intra-person emotion inducers at work (Thompson et al, 2016), we identify an interpersonal emotion of being envied inducer (i.e., LMX), adding a significant piece of knowledge to the emotion literature.…”
mentioning
confidence: 99%
“…In fact, envy affects human relationships, generating hostility, competition between colleagues, or aggressive behaviors (see [ 5 ]). Envy is defined by Vecchio [ 6 ] as a “pattern of thoughts, emotions, and behaviors that result from an employee’s loss of self-esteem in response to a referent other’s obtainment of outcomes that one strongly desires” (p. 162).…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished by either moving oneself up or pulling the other person down. In fact, previous research proposes envy as an antecedent of counterproductive work behavior (CWB) [ 5 , 7 , 8 ]. In the workplace, CWB are defined as actions directed towards other members of the organization with the objective of hurting them through threats, nasty comments, and ridicule, or by damaging their performance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation